Luxury brands in the South African emerging market: an empirical study ot the relationship between consumer personality traits and purchase intentions towards luxury brands - Bills, Ashleigh (The IIE, 2017)
Luxury brand consumption has flourished worldwide over the last decade. Traditionally there has been great emphasis on research investigating western emerged luxury brand markets. Increasingly however, a strong desire for luxury brands in emerging societies has become conspicuous, yet literature focusing on these markets remains marginal. While certain personality commonalities may exist across emerged and emerging consumers, aspects that may influence purchasing behaviour in one cultural group may not be relevant to another culture. The underlying theme in this research paper therefore, is to investigate the relationship of personality for South African consumers and their purchase intentions towards luxury brands within an emerging market context. The personality factors that were chosen as predictors of South African consumer’s purchase intentions towards luxury brands were; need for materialism, need for uniqueness, need for status/conspicuousness and need for social comparison. This study took a quantitative approach with an online questionnaire serving as the main form of data collection. Through the use of snowball sampling, a sample of 60 respondents was received. Results of the study revealed that all of the selected personality traits were correlated with South African consumers purchase intentions towards luxury brands. Need for materialism and need for uniqueness were discovered to be the most predominant predictors. This study has helped advance the existing knowledge relating to emerging markets, particularly the South African market, and their purchase intentions. Additionally this knowledge will contribute to local and global luxury brands and the influence of personality traits within their branding strategies towards South African consumer.
Keywords: Brands; Branding; Luxury Brands; Consumer Behaviour